Study Of Work Reliability Synchronology Generator Unit PLTMH Aek Raisan I North Tapanuli - Rahmad Dani; Solly Aryza; Siti Anisah (INFOKUM, 2021)
The Mini-hydro Power Plant (PLTMH) located in Parsingkaman Village, North Tapanuli Regency is a power plant with a capacity that is not too high. It was built with the aim of meeting the needs of electrical energy in North Tapanuli Regency which often experiences blackouts. The purpose of this study is to determine the performance of the generator in generating electrical energy. Data collection is done by direct observation in the field. The results showed that the peak load of the generator was 657,359.3 KW, a small load of 604,482,365 W. With the efficiency of the synchronous generator, which was 85.6%, with these results that the generator contained in the AEK RAISAN I PLTMH was still efficiently used.